Peran Pemasaran Digital di Kelurahan Pesantren Kecamatan Mijen Sermarang - Sulistiyani; Amsar; Muchayatin; Camilius; Yuniarto, Galuh (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
This community service is carried out with the aim of improving marketing skills in using social media or internet media in the Pesantren sub-district community, Mijen district, Semarang. Digital marketing has become crucial for business actors in the digital era, especially small and medium enterprises (SMEs) who want to increase their market share effectively and efficiently. The purpose of this service is to help SMEs in Semarang City understand and implement digital marketing strategies, and digital advertising. Through training and coaching, SMEs learn the importance of producing high-quality content, interacting with customers online, and utilizing analytical data to increase the effectiveness of marketing campaigns. The results of the activity show that SMEs have become more knowledgeable and proficient in handling digital platforms, and that the implementation of recommended strategies has increased engagement and revenue.